2021
DOI: 10.1097/ta.0000000000003145
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital tourniquet use: An evaluation of community application and outcome

Abstract: BACKGROUND:There is substantial investment in layperson and first responder training involving tourniquet use for hemorrhage control. Little is known however about prehospital tourniquet application, field conversion, or outcomes in the civilian setting. We describe the experience of a metropolitan region with prehospital tourniquet application. METHODS:We conducted a retrospective cohort study characterizing prehospital tourniquet use treated by emergency medical services (EMS) in King County, Washington, fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Studies have shown that tourniquet usage in rural settings can be beneficial. Tourniquets have equalized rural morbidity and mortality compared to urban settings, 38 though its utility does depend on hospital transfer times not being increased 39 . Most significantly, prior literature has documented significant reductions in civilian mortality (1% and 9%) due to prehospital tourniquet use, 37,40 along with a reductions in limb amputations (8%) and fasciotomies (19%) in an 8‐year retrospective study 41 …”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that tourniquet usage in rural settings can be beneficial. Tourniquets have equalized rural morbidity and mortality compared to urban settings, 38 though its utility does depend on hospital transfer times not being increased 39 . Most significantly, prior literature has documented significant reductions in civilian mortality (1% and 9%) due to prehospital tourniquet use, 37,40 along with a reductions in limb amputations (8%) and fasciotomies (19%) in an 8‐year retrospective study 41 …”
Section: Discussionmentioning
confidence: 99%
“…22,23 A growing body of literature has shown the safety and impact of prehospital tourniquets. 24,25 Smith et al found that prehospital tourniquets were safely used to control bleeding in major extremity penetrating trauma without increased risk of major complications and were also associated with increased systolic blood pressure on arrival to the emergency department, decreased blood product use, and decreased incidence of limb-related complications. 26 Bonk et al reviewed autopsy records and estimated 235 isolated extremity injury-related deaths could be prevented and an additional estimated 4354 concurrent extremity and central injury-related deaths could potentially receive enhanced care with early tourniquet placement.…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of literature has shown the safety and impact of prehospital tourniquets 24,25 . Smith et al found that prehospital tourniquets were safely used to control bleeding in major extremity penetrating trauma without increased risk of major complications and were also associated with increased systolic blood pressure on arrival to the emergency department, decreased blood product use, and decreased incidence of limb‐related complications 26 .…”
Section: Introductionmentioning
confidence: 99%